Semiotics and the Grotesque in Political Cartoons - Timothy David Smith (Semiotic Review)
Through cartoonish distortion, grotesquery, and comedy, the art of caricature signals a lack of seriousness. Despite such appearances, I argue that editorial caricature is a valuable source of historical evidence that gestures toward the intersubjectivity of audience, production, and text. This dynamic interface presupposes complex cultural literacies required to “read” these cartoons. To the historian, editorial caricature presents unique insight into an artist’s imaginative appeal to a contemporaneous audience. In this article, I survey the features and expressions of the art of the caricature from sixteenth century Italy through the late Antebellum United States. I pair this brief historiography with interdisciplinary theory and an analysis of an 1856 editorial caricature by Philadelphia lithographer John L. Magee. I triangulate my analysis with inquiry in the arts and media of the period. My investigation yields evidence of patterns in this hybrid, verbal-visual discourse that recapitulate regional, national, and transnational themes. I argue that Magee’s meaning-making process in his graphic political satire titled “Forcing Slavery Down the Throat of a Freesoiler” mobilizes complex cultural matrices to identify prominent Northern Democrats as a grievous threat to the free-soil ideals adopted by an emergent Republican party. Magee’s complex, narrative and semiotic elaborations offer historical evidence of editorial caricature’s interactivity with ideology, politics, and rhetoric across both verbal and visual fields.